2022
DOI: 10.1111/jace.18389
|View full text |Cite
|
Sign up to set email alerts
|

Contact damage tolerance of alumina‐based layered ceramics with tailored microstructures

Abstract: This work demonstrates how to enhance contact damage resistance of aluminabased ceramics combining tailored microstructures in a multilayer architecture. The multilayer system designed with textured alumina layers under compressive residual stresses embedded between alumina-zirconia layers was investigated under Hertzian contact loading and compared to the corresponding monolithic reference materials. Critical forces for crack initiation under spherical contact were detected through an acoustic emission system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…5,6,8,9 F I G U R E 3 Crack initiation forces 𝐹 𝑐 normalized by ball radii 𝑅 𝑏 for indentation of ceramics by various balls. 11,12,13,2 indented by diamond balls, 11 and 10%-26% for soda-limesilica glass indented by tungsten carbide balls, 15 among others. Recent work from Schlacher et al 2 showed that for Al 2 O 3 and Si 3 N 4 indented by WC balls cracks may be 20%-40% larger than the contact radius (Figure 4), which seems inconsistent with other reported values.…”
Section: Location Of Ring Crack Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,8,9 F I G U R E 3 Crack initiation forces 𝐹 𝑐 normalized by ball radii 𝑅 𝑏 for indentation of ceramics by various balls. 11,12,13,2 indented by diamond balls, 11 and 10%-26% for soda-limesilica glass indented by tungsten carbide balls, 15 among others. Recent work from Schlacher et al 2 showed that for Al 2 O 3 and Si 3 N 4 indented by WC balls cracks may be 20%-40% larger than the contact radius (Figure 4), which seems inconsistent with other reported values.…”
Section: Location Of Ring Crack Formationmentioning
confidence: 99%
“…11,12,13,2 indented by diamond balls, 11 and 10%-26% for soda-limesilica glass indented by tungsten carbide balls, 15 among others. Recent work from Schlacher et al 2 showed that for Al 2 O 3 and Si 3 N 4 indented by WC balls cracks may be 20%-40% larger than the contact radius (Figure 4), which seems inconsistent with other reported values. In the case of Si 3 N 4 indented by WC balls, additional experiments were done to analyze the effect of friction due to contact.…”
Section: Location Of Ring Crack Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[37,51,53] This concept has been recently demonstrated, both under bending and contact loading, in tape-casted alumina-based layered ceramics designed with "textured" layers embedded between "equiaxed" layers. [54,55] In this regard, there is a great potential for employing additive manufacturing techniques, based on layer-by-layer deposition methods, to fabricate 3D-printed multilayer architectures (of different complexity) with improved fracture resistance and guaranteed minimum strength. The "multimaterial" approach aiming to tailor the microstructure of the parts by combining materials during the printing work has already been successfully employed in recent years; some examples will be presented in the next section.…”
Section: Microstructural Designmentioning
confidence: 99%
“…[ 37,51,53 ] This concept has been recently demonstrated, both under bending and contact loading, in tape‐casted alumina‐based layered ceramics designed with “textured” layers embedded between “equiaxed” layers. [ 54,55 ]…”
Section: Opportunities For the Design Of Damage Tolerant 3d‐printed C...mentioning
confidence: 99%